Generational differences in workplace communication - Abdul Malek, Marlin Marissa; Jaguli, Abd Rahim (John Benjamins Publishing Company, 2018)
Purpose – This research investigates the generational differences in workplace communication, expectations and behaviors of employees from the perspectives of female leaders and their direct reports.Design – This study employs a qualitative approach through in-depth interviews with 12 female leaders and 24 of their direct reports who are working in various organizations in Malaysia.Findings – Findings include three themes that emerged as key in determining and reflecting the female leaders’ experiences in communicating with their employees in the workplace: (1) attitudes towards power and authority; (2) being creative and taking risks and (3) workplace dynamics.Research Implications – The workplace setting and the leaders’ stance with regards to workplace interaction have seen adjustment towards a flatter and less-hierarchical structure in line with the challenges associated with the 21st century organizations.Practical implications – Leaders and members of the organizations should work towards balancing some traditional and emerging expectations and work practices to better engage with each other. Originality/value – This research highlights the interactions between two distinct groups that are gaining importance and influence in the current workplace; female leaders and the Gen-Ys and uncovers the unique blend between perceived cultural dimensions, the influence of technology advancement and overseas exposure in organizations in Malaysia.